2023
DOI: 10.9734/ijpss/2023/v35i92908
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Nitrogen and Weed Management Practices on Yield and Economics of Blackgram (Vigna mungo L.)

Abstract: In Kharif 2022, a research study was conducted at Crop Research Farm, SHUATS, Prayagraj to investigate the “Influence of nitrogen and weed management practices on yield and economics of Blackgram (Vigna mungo L.)”. The study included three levels of nitrogen (15, 30, and 45 kg/ha) and three weed management practices (hand weeding twice at 20 and 40 DAS, Pendimethalin pre-emergence at 5 DAS, and Imazethapyr post-emergence at 25 DAS). The experiment was designed using a randomized block design with 10 treatments… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 5 publications
0
0
0
Order By: Relevance
“…This might be due to effective control of weeds reduce the crop weed competition, increased maximum availability of moisture, nutrient, space and light, to the plant resulted in higher crop growth and protein yield. Shekara et al [15] also reported the similar type of responses [16][17][18][19][20].…”
Section: Discussionmentioning
confidence: 83%
“…This might be due to effective control of weeds reduce the crop weed competition, increased maximum availability of moisture, nutrient, space and light, to the plant resulted in higher crop growth and protein yield. Shekara et al [15] also reported the similar type of responses [16][17][18][19][20].…”
Section: Discussionmentioning
confidence: 83%